2017
DOI: 10.1128/cmr.00019-17
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Maturational Neonatal Immune Deficiencies and Susceptibility to Group B Streptococcus Infection

Abstract: Although a normal member of the gastrointestinal and vaginal microbiota, group B (GBS) can also occasionally be the cause of highly invasive neonatal disease and is an emerging pathogen in both elderly and immunocompromised adults. Neonatal GBS infections are typically transmitted from mother to baby either or during passage through the birth canal and can lead to pneumonia, sepsis, and meningitis within the first few months of life. Compared to the adult immune system, the neonatal immune system has a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 161 publications
(171 reference statements)
1
27
0
4
Order By: Relevance
“…One of the most well-studied virulence factors of GBS is its unique sialic acid-rich capsular polysaccharide (CPS) which inhibits complement deposition and protects the bacteria from opsonophagocytosis by immune cells, thus contributing to the evasion of host immune defense mechanisms. 30,31 The CPS also enhances biofilm formation, inhibits the binding of antimicrobial peptides and neutrophil extracellular traps (NET) as well as disturbing bacterial adherence to the epithelium and mucus, thus increasing GBS invasiveness. [32][33][34][35][36][37][38] GBS expresses 10 types of CPS (Ia, Ib, II-IX) that are structurally and antigenically different.…”
Section: Capsular Polysaccharide Conjugate Vaccinesmentioning
confidence: 99%
“…One of the most well-studied virulence factors of GBS is its unique sialic acid-rich capsular polysaccharide (CPS) which inhibits complement deposition and protects the bacteria from opsonophagocytosis by immune cells, thus contributing to the evasion of host immune defense mechanisms. 30,31 The CPS also enhances biofilm formation, inhibits the binding of antimicrobial peptides and neutrophil extracellular traps (NET) as well as disturbing bacterial adherence to the epithelium and mucus, thus increasing GBS invasiveness. [32][33][34][35][36][37][38] GBS expresses 10 types of CPS (Ia, Ib, II-IX) that are structurally and antigenically different.…”
Section: Capsular Polysaccharide Conjugate Vaccinesmentioning
confidence: 99%
“…The role of on February 21, 2021 by guest http://iai.asm.org/ Downloaded from macrophages in responding to both neonatal and in utero infections is of particular relevance. Because neonates initially have an immature adaptive immune system, they rely heavily on the innate immune system, in which macrophages play a central role, to combat bacterial infections (5). Additionally, macrophages are one of the most prevalent immune system cells at the maternal-fetal interface, where they promote maternal tolerance to the developing fetus and destroy pathogens that have crossed the extraplacental membranes (6).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, prior studies have shown that inappropriate inflammatory signaling can contribute to adverse pregnancy outcomes such as extraplacental membrane weakening and neonatal sepsis [3,4]. The macrophage response is of particular importance for neonates, whose immature adaptive immune system forces them to rely primarily on the innate immune system to combat bacterial infections [5]. Macrophages are also present at the maternal fetal interface where they aid in the maintenance of maternal tolerance to the developing fetus and combat pathogens that have crossed the extraplacental membranes [6].…”
Section: Introductionmentioning
confidence: 99%